DISIPLIN KERJA DI MATA KARYAWAN DAN IMPLEMENTASINYA - Harras, Hadyati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Discipline is an organization attitude, whose mistakes affect balance. Even in the worst cases, discipline can damage the environment. This condition should be avoided. Because really discipline is the attitude of success. This study aims to explore information about discipline, especially individually, how and what discipline they have. The method used in this research is survey. Then the derivatives use observation, in it there is an interview. The results of the study revealed, 1) the background dominated the attitude of the discipline. 2) knowledge or education strengthen discipline. and 3) rules are instructions on how to be disciplined. This confirms, discipline in principle the individual part. Therefore placing and treating it must be a humanitarian approach. However, organizations can mix disciplines as the goals of the organization